2016
DOI: 10.15252/emmm.201606255
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial calcium uniporter regulates breast cancer progression via HIF ‐1α

Abstract: Triple‐negative breast cancer (TNBC) represents the most aggressive breast tumor subtype. However, the molecular determinants responsible for the metastatic TNBC phenotype are only partially understood. We here show that expression of the mitochondrial calcium uniporter (MCU), the selective channel responsible for mitochondrial Ca2+ uptake, correlates with tumor size and lymph node infiltration, suggesting that mitochondrial Ca2+ uptake might be instrumental for tumor growth and metastatic formation. According… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
276
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 217 publications
(297 citation statements)
references
References 54 publications
19
276
2
Order By: Relevance
“…The following plasmids were used and are described elsewhere: 2mtGCaMP6m 29,61, 4mtGCaMP6f 62, mtAeq 63, MICU1-HA 29, MICU1-Flag 29, MICU2-Flag 29, MICU1 C465A -HA 29, MCU-Flag 15, GCaMP6f, a kind gift from Douglas Kim (Addgene plasmid # 40755) and R-GECO1, a kind gift from Robert Campbell (Addgene plasmid # 32444)64. The MICU3-myc chimera was produced by gene synthesis (ThermoFisher Scientific) using the coding sequence derived from NM_030110, and cloned into pcDNA3.1.…”
Section: Methodsmentioning
confidence: 99%
“…The following plasmids were used and are described elsewhere: 2mtGCaMP6m 29,61, 4mtGCaMP6f 62, mtAeq 63, MICU1-HA 29, MICU1-Flag 29, MICU2-Flag 29, MICU1 C465A -HA 29, MCU-Flag 15, GCaMP6f, a kind gift from Douglas Kim (Addgene plasmid # 40755) and R-GECO1, a kind gift from Robert Campbell (Addgene plasmid # 32444)64. The MICU3-myc chimera was produced by gene synthesis (ThermoFisher Scientific) using the coding sequence derived from NM_030110, and cloned into pcDNA3.1.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent studies on MCU and MICU1 in mammalian cells showed an evolutionarily conserved contribution of the mitochondrial Ca 2+ uptake machinery in cell migration. Indeed, in endothelial36 or breast37 and cervical cancer38 cells, alteration of the mitochondrial Ca 2+ uptake led to similar defects in migration abilities. Finally, computed data from clinical studies suggested that mcu -overexpression and micu1 -under expression were associated with poor prognosis for breast cancer patients3839.…”
mentioning
confidence: 95%
“…However, there is no direct evidence associating MCU downregulation with carcinogenesis. On the contrary, studies have shown that expression of MCU correlates positively with tumor size and lymph node infiltration in triple-negative breast cancer, demonstrating that mitochondrial Ca 2þ uptake is important for tumor growth and metastasis (44). Other experiments demonstrated that MCU is important for survival and migration of breast carcinoma cells (25,27).…”
Section: Discussionmentioning
confidence: 99%